Apparent lack of evidence on selected infectious agents in wild Yellow-naped Amazon parrots: implications for releasing attempts - Dolz, Gaby (2015)
Blood and feather samples, as well as oropharyngeal and cloacal swabs, were collected from nine free-ranging Amazona auropalliata between January and May 2009 in two highly modified landscapes in northern Costa Rica. Samples were tested for avian circovirus, avian polyomavirus, avian influenza, Chlamydophila psittaci, Borrelia burgdorferi sensu lato, and Rickettsia spp. All samples were negative. Results are discussed in terms of implications of using captive birds for reintroduction attempts into wild populations in Costa Rica.